Susceptibility of neuron-like cells derived from bovine Wharton's jelly to bovine herpesvirus type 5 infections - Cardoso, Tereza C. [UNESP]; Novais, Juliana B. [UNESP]; Antello, Talita F. [UNESP]; Silva-Frade, Camila [UNESP]; Ferrarezi, Marina C. [UNESP]; Ferrari, Heitor F. [UNESP]; Gameiro, Roberto [UNESP]; Flores, Eduardo F. [UNESP] (Biomed Central Ltd., 2012)
Background: Bovine herpesvirus type 5 (BoHV-5), frequently lethal in cattle, is associated with significant agricultural economic losses due to neurological disease. Cattle and rabbits are frequently used as models to study the biology and pathogenesis of BoHV-5 infection. In particular, neural invasion and proliferation are two of the factors important in BoHV-5 infection. The present study investigated the potential of bovine Wharton's jelly mesenchymal stromal cells (bWJ-MSCs) to differentiate into a neuronal phenotype and support robust BoHV-5 replication.Results: Upon inducing differentiation within a defined neuronal specific medium, most bWJ-MSCs acquired the distinctive neuronal morphological features and stained positively for the neuronal/glial markers MAP2 (neuronal microtubule associated protein 2), N200 (neurofilament 200), NT3 (neutrophin 3), tau and GFAP (glial fibrillary acidic protein). Expression of nestin, N200, beta-tubulin III (TuJI) and GFAP was further demonstrated by reverse transcriptase polymerase chain reaction (RT-PCR). Following BoHV-5 inoculation, there were low rates of cell detachment, good cell viability at 96 h post-infection (p.i.), and small vesicles developed along neuronal branches. Levels of BoHV-5 antigens and DNA were associated with the peak in viral titres at 72 h p.i. BoHV-5 glycoprotein C mRNA expression was significantly correlated with production of progeny virus at 72 h p.i. (p < 0.05).Conclusion: The results demonstrated the ability of bWJ-MSCs to differentiate into a neuronal phenotype in vitro and support productive BoHV-5 replication. These findings constitute a remarkable contribution to the in vitro study of neurotropic viruses. This work may pave the way for bWJ-MSCs to be used as an alternative to animal models in the study of BoHV-5 biology.
Keywords: BoHV-5; in vitro replication; Neuronal culture